Rapid microwave assisted synthesis of AgNPs using Acacia ferruginea leaf extract and strategic interventions against the microbial symphony - Jeevitha M.; Vinodhini Subramaniyam; Moorthi Pichumani; Shubashini K. Sripathi (Next Nanotechnology)
Nanoparticles (NPs) are tiny materials with a high reactive surface area, which is measured in the nm scale. Nanotechnology paves the way to produce and explore the unique physicochemical properties of nanoparticles. Using plant extracts to produce silver nanoparticles (AgNPs) offers a promising alternative to traditional chemical synthesis methods. This study utilized aqueous and ethanolic leaf extracts of Acacia ferruginea to produce AgNPs and examined their anti-microbial sensing activity against C. violaceum and P. aeruginosa. The UV–vis spectrum of AgNPs showed an absorption peak (SPR band) between 420 – 457 nm, while HR-TEM revealed spherical particles with an average size of 13.65 nm. FTIR analysis identified prominent bioactive compounds crucial for the reduction and capping processes. X-ray diffraction (XRD) confirmed the crystalline nature of the AgNPs, with a face-centered cubic (fcc) structure. The nanoparticles were small and spherical (average size 13.65 nm), with a large truncated octahedron shape as per HR-TEM analysis. The zeta potential readings were – 5.9 mV for ethanolic extract and – 26.1 mV for aqueous extract, indicating good stability. DLS results showed zeta potential and Z-average sizes of – 9.4 mV and 22.3 nm for the nanoparticles. FE-SEM analysis provided average sizes of 79.83 nm for AFLAqNPs and 37.72 nm for AFLENPs. From the HPLC analysis, notable peaks were observed at 201, 264, and 408 nm. The DPPH method confirmed the antioxidant activity of the AgNPs. EDS data indicated that the nanoparticles contained pure silver. The synthesized AgNPs demonstrated potent anti-microbial activity against Chromobacterium violaceum and Pseudomonas aeruginosa, suggesting potential applications in developing novel medications for managing P. aeruginosa infections. Future research could explore the use of these nanoparticles in targeted drug delivery and antimicrobial coatings in various medical fields.